2020
DOI: 10.1002/ags3.12374
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using a perioperative artificial endocrine pancreas in pancreatic resection

Abstract: Surgical operations exert considerable physical stress on patients perioperatively, and recent studies demonstrated that hyperglycemia exacerbates the inflammatory response and leads to oxidative stress, poor immune function, and endothelial dysfunction. 1,2 Hyperglycemia is a risk factor for infectious diseases and results in increased comorbidities and mortality, and maintenance of blood glucose levels at <180 mg/dL has been recommended. 3 A previous retrospective study reported that in a comparison of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(47 reference statements)
1
3
0
1
Order By: Relevance
“…Some recent reports 14‐17 supported our previous data that perioperative strict glycemic control using a bedside AP was useful in improving surgical outcomes after gastroenterological surgeries. Hayashi et al 14 suggested that perioperative IIT using an AP was safe, with no hypoglycemia in 50 patients undergoing pancreatoduodenectomy (PD) (n = 24), major hepatectomy (n = 22), and liver transplantations (n = 4).…”
Section: Current Bedside Ap Stg‐55 With Closed‐loop Systemsupporting
confidence: 68%
See 2 more Smart Citations
“…Some recent reports 14‐17 supported our previous data that perioperative strict glycemic control using a bedside AP was useful in improving surgical outcomes after gastroenterological surgeries. Hayashi et al 14 suggested that perioperative IIT using an AP was safe, with no hypoglycemia in 50 patients undergoing pancreatoduodenectomy (PD) (n = 24), major hepatectomy (n = 22), and liver transplantations (n = 4).…”
Section: Current Bedside Ap Stg‐55 With Closed‐loop Systemsupporting
confidence: 68%
“…Hayashi et al 14 suggested that perioperative IIT using an AP was safe, with no hypoglycemia in 50 patients undergoing pancreatoduodenectomy (PD) (n = 24), major hepatectomy (n = 22), and liver transplantations (n = 4). Yoshimoto et al 15 reported that perioperative AP treatment was safe without hypoglycemia and significantly reduced serious complications (Clavien‐Dindo grade >IIIa) after pancreatectomy. Akabori et al 16 demonstrated that AP facilitated strict and safe glycemic control while reducing inflammatory mediators, including adiponectin, after PD.…”
Section: Current Bedside Ap Stg‐55 With Closed‐loop Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Die postoperative glykämische Kontrolle bei Herz-Thoraxchirurgie konnte in einer weiteren Arbeit mittels Bedside-AI verbessert werden, wobei die Ergebnisse unabhängig vom Diabetesstatus des eingeschlossenen Kollektivs waren [ 156 ]. Es wird darüber hinaus postuliert, dass durch den perioperativen Einsatz des oben angeführten künstlichen Pankreassystems postoperative Komplikationen reduziert werden könnten [ 157 , 158 ]. Eine andere Studie zeigte bei einem kardiochirurgischen Kollektiv, dass automatisierte intravenöse Insulinzufuhr die Patient:innen im glykämischen Zielbereich halten konnte ohne Hypoglykämien zu erhöhen [ 159 ].…”
Section: Perioperative Medikamentöse Diabetestherapieunclassified
“…In another study, an early postoperative glucose level of higher than 140 mg/dL was significantly associated with postoperative complications in patients with and without DM [ 9 ]. The intensive SGL control group had significantly fewer bile leaks, pancreatic fistulae, and hospitalizations than the intermediate glucose control group, in an artificial endocrine pancreas study for patients who received a pancreatic resection; complications with a Clavien-Dindo classification (CDc) of higher than grade III occurred significantly less in the group whose target was 120–180 mg/dL [ 10 , 11 ]. Other studies have shown that an artificial pancreas promotes tight and safe glycemic control while reducing anti-inflammatory mediators, including adiponectin, after pancreaticoduodenectomy (PD) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%